Избавиться от иррациональности в знаменателе дроби 1/√3-1
Избавиться от иррациональности в знаменателе дроби 1/√3-1
Ответ(ы) на вопрос:
1/sqrt(3)-1
sqrt(3)+1/3-1
sqrt(3)+1/2
Или при другом условии:
1/sqrt(3-1)
sqrt(3-1)/3-1
sqrt(2)/2
[latex] \frac{1}{ \sqrt{3}-1 } = \frac{1}{ \sqrt{3}-1 } *\frac{ \sqrt{3}+ 1}{ \sqrt{3}+1 } = \frac{ 1*(\sqrt{3}+1) }{( \sqrt{3}-1 )*( \sqrt{3} +1)} = \frac{ \sqrt{3} +1}{( \sqrt{3} )^2-1^2}= \frac{ \sqrt{3} +1}{3-1}= \frac{ \sqrt{3}+1 }{2}[/latex]
Не нашли ответ?
Похожие вопросы